Abiotic stress-induced secondary metabolite production in Brassica: opportunities and challenges - Muthusamy, Muthusamy; Lee, Soo In (Frontiers in Plant Science, 2024)
Over the decades, extensive research efforts have been undertaken to understand how secondary plant metabolites are affected by genetic, environmental, and agronomic factors. Understanding the genetic basis of stress-response metabolite biosynthesis is crucial for sustainable agriculture production amidst frequent occurrence of climatic anomalies. Although it is known that environmental factors influence phytochemical profiles and their content, studies of plant compounds in relation to stress mitigation are only emerging and largely hindered by phytochemical diversities and technical shortcomings in measurement techniques. Despite these challenges, considerable success has been achieved in profiling of secondary metabolites such as glucosinolates, flavonoids, carotenoids, phenolic acids and alkaloids. In this study, we aimed to understand the roles of glucosinolates, flavonoids, carotenoids, phenolic acids and alkaloids in relation to their abiotic stress response, with a focus on the developing of stress-resilient crops. The focal genus is the Brassica since it (i) possesses variety of specialized phytochemicals that are important for its plant defense against major abiotic stresses, and (ii) hosts many economically important crops that are sensitive to adverse growth conditions. We summarize that augmented levels of specialized metabolites in Brassica primarily function as stress mitigators against oxidative stress, which is a secondary stressor in many abiotic stresses. Furthermore, it is clear that functional characterization of stress-response metabolites or their genetic pathways describing biosynthesis is essential for developing stress-resilient Brassica crops.